Health preserving agent suitable for cement stabilized macadam of pavement base in Qinghai-Tibet alpine region and preparation method of health preserving agent

By preparing a health agent containing cross-linked sodium polyacrylate-cellulose nanofiber composite water-retaining microcapsules, the problem of moisture retention and freezing in the construction of cement-stabilized gravel on the pavement base in Qinghai-Tibet High-altitude Zone was solved, and efficient hydration reaction and anti-freeze-thaw performance were achieved, and construction quality and durability were improved.

CN120364973APending Publication Date: 2025-07-25QINGHAI UNIV OF SCI & TECH (UNDER PREPARATION)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510501067.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-21
Publication Date
2025-07-25

AI Technical Summary

Technical Problem

It is difficult for existing health agents to retain moisture in low temperature environments during the construction of cement-stabilized gravel on the pavement base of the Qinghai-Tibet High-altitude Zone, resulting in insufficient hydration reaction and susceptible to freezing and swelling damage. It is difficult for the existing preparation methods to effectively compound a variety of functional materials.

Method used

Health agents composed of crosslinked sodium polyacrylate-cellulose nanofiber composite water-retaining microcapsules, short-chain organic phase change material microcapsules, nano-hydroxyapatite, alkali-activated blast furnace slag powder, low-temperature early strength composite agent, environmentally friendly antifreeze long-acting agent and polycarboxylic acid-based high-efficiency water reducer are formed through microencapsulation, composite colloid preparation and spray drying, a three-dimensional network structure and antifreeze film are formed to promote hydration reaction and inhibit ice crystal formation.

Benefits of technology

It significantly improves the water retention rate and early strength of the cement base layer, reduces the loss of freeze-thaw cycle, improves construction performance and durability, and meets the construction needs of the Qinghai-Tibet High-altitude Zone.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120364973A_ABST
    Figure CN120364973A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of health preserving agents, and particularly discloses a health preserving agent suitable for cement stabilized macadam of a pavement base in a Qinghai-Tibet alpine region and a preparation method of the health preserving agent. Comprising 35%-40% of crosslinked sodium polyacrylate-cellulose nanofiber composite water retention microcapsules, 5%-8% of short-chain organic phase change material microcapsules, 3%-5% of nano-hydroxyapatite, 20%-25% of alkali activated blast furnace slag powder, 0.5%-1% of graphene oxide aqueous dispersion, 8%-10% of a low-temperature early strength complexing agent, 6%-9% of an environment-friendly antifreeze long-acting agent and 1%-1% of a polycarboxylate superplasticizer. 2%, 0.5%-1% of an auxiliary stabilizer; the phase-change fatty acid absorbs and releases latent heat in the thawing / solidification process, the instantaneous temperature change during construction and freezing and thawing circulation can be effectively buffered, and thermal stress concentration is reduced; the propylene glycol and the organic silicon emulsion form an anti-freezing film in a water phase and reduce the freezing point of water in capillary pores, and cooperate with the phase change material to jointly inhibit generation of ice crystals and relieve frost heaving damage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of the preparation of curing agents, and particularly relates to a curing agent applicable to cement stabilized macadam for the road surface base layer in the Qinghai-Tibet alpine region and a preparation method thereof. Background Art

[0002] When constructing the cement stabilized macadam for the road surface base layer in the Qinghai-Tibet alpine region, many severe challenges are faced. The temperature difference between day and night in this region is extremely large. When the temperature is relatively high during the day, the water evaporates rapidly, while the temperature drops sharply at night, which is extremely likely to cause the water during the curing process to freeze, thereby damaging the structure of the cement stabilized macadam base layer. Traditional curing methods, such as watering curing and covering with curing membranes, have obvious deficiencies in the alpine environment. In the case of watering curing under low-temperature conditions, it is difficult to effectively retain the water, and it is easy to freeze. Not only can it not play a curing role, but it may also cause frost heaving damage to the base layer; although covering with a curing membrane can reduce the water evaporation to a certain extent, in an environment with strong winds and large temperature differences between day and night, the water inside the membrane will still quickly dissipate, and at the same time, the fixation and replacement of the curing membrane also face many difficulties, increasing the construction cost and labor intensity.

[0003] From the perspective of the curing agent materials themselves, some existing curing agents are difficult to meet the special requirements of the Qinghai-Tibet alpine region in terms of performance. Some curing agents have poor water retention performance and cannot continuously provide sufficient water for the cement stabilized macadam base layer for a long time, resulting in insufficient hydration reaction of cement and affecting the strength development of the base layer; some curing agents have poor frost resistance in low-temperature environments and cannot effectively inhibit the formation of ice crystals, causing serious damage to the base layer during the freeze-thaw cycle; there are also some curing agents with problems in construction adaptability, such as poor compatibility with the cement stabilized macadam base layer, resulting in slurry stratification and precipitation, affecting the curing effect; or poor synergistic effect with admixtures such as water reducers, unable to achieve the best construction performance and curing effect.

[0004] In addition, the existing preparation methods of curing agents are relatively simple, and it is difficult to effectively compound a variety of functional materials to give full play to the advantages of each material. For example, during the preparation process, the dispersion treatment of nano materials and mineral powders is not fine enough, resulting in serious particle agglomeration, and it is impossible to form a continuous and dense hydration product layer at the entire aggregate-slurry interface, thus affecting the overall performance of the base layer. Therefore, it is of great practical significance to develop a special curing agent applicable to cement stabilized macadam for the road surface base layer in the Qinghai-Tibet alpine region and an efficient preparation method thereof.

[0005] In view of this, the inventor proposes a curing agent applicable to cement stabilized macadam for the road surface base layer in the Qinghai-Tibet alpine region and a preparation method thereof to solve the above problems. Summary of the Invention

[0006] The purpose of the present invention is to provide a curing agent for cement-stabilized macadam for the road surface base layer in the Qinghai-Tibet alpine region and its preparation method, so as to solve the problems put forward in the above-mentioned background technology.

[0007] To achieve the above purpose, the present invention provides the following technical solutions:

[0008] A curing agent for cement-stabilized macadam for the road surface base layer in the Qinghai-Tibet alpine region, the curing agent includes by mass percentage:

[0009] Crosslinked sodium polyacrylate-cellulose nanofiber composite water-retaining microcapsules 35% - 40%, short-chain organic phase change material microcapsules 5% - 8%, nano-hydroxyapatite 3% - 5%, alkali-activated blast furnace slag powder 20% - 25%, graphene oxide aqueous dispersion 0.5% - 1%, low-temperature early strength composite agent 8% - 10%, environmentally friendly anti-freezing long-acting agent 6% - 9%, polycarboxylate-based high-range water reducer 1% - 2%, auxiliary stabilizer 0.5% - 1%.

[0010] Preferably, the low-temperature early strength composite agent is nano-calcium oxide and magnesium sulfate, and the mass fraction percentages of nano-calcium oxide and magnesium sulfate are 60% and 40% respectively;

[0011] The environmentally friendly anti-freezing long-acting agent is propylene glycol and silicone emulsion, and the mass fraction percentages of propylene glycol and silicone emulsion are 65% and 35% respectively;

[0012] The auxiliary stabilizer is crosslinked carboxymethyl cellulose and borax, and the mass fraction percentages of crosslinked carboxymethyl cellulose and borax are 70%:30% respectively.

[0013] A preparation method of a curing agent for cement-stabilized macadam for the road surface base layer in the Qinghai-Tibet alpine region, including the following steps:

[0014] S1. Microencapsulation of water-retaining matrix: Mix crosslinked sodium polyacrylate and cellulose nanofibers in deionized water at a solid-water ratio of 1:10, heat to 60°C and stir for 45 min, and perform spray microencapsulation to obtain water-retaining microcapsule powder;

[0015] S2. Microencapsulation of phase change material: Dissolve short-chain saturated fatty acid phase change material in hexane, emulsify it with 1 wt% chitosan aqueous emulsion under a shear emulsifier, add glutaraldehyde for crosslinking, let it stand for 2 h, elute the solvent and dry to obtain phase change microcapsule powder;

[0016] S3. Preparation of composite colloid: Add the water-retaining microcapsule powder and the phase change microcapsule powder to the aqueous phase at a mass ratio of 1:4, stir at 50°C and 800 rpm for 30 min to obtain a water-retaining-phase change composite colloid;

[0017] S4, Nano - Mineral Dispersion: Sequentially add alkali - activated blast furnace slag powder, nano - hydroxyapatite with a solid content of 30%, and 0.8% graphene oxide dispersion to the water - retaining phase - change composite colloid, and perform ultrasonic dispersion treatment to obtain a nano - mineral homogeneous slurry;

[0018] S5, Functional Agent Composite: Mix the low - temperature early - strength composite agent and the environmental protection anti - freezing long - acting agent in a ratio of 1:1 and drop - add them to the nano - mineral homogeneous slurry, and stir at 40°C and 600 rpm for 20 min to obtain a multi - functional composite slurry;

[0019] S6, Construction Adaptability Optimization: Add a polycarboxylate - based high - range water - reducer and an auxiliary stabilizer to the multi - functional composite slurry, and stir at room temperature of 200 rpm for 10 min to obtain a slurry with optimized construction adaptability;

[0020] S7, Spray Drying: Dry the slurry with optimized construction adaptability in a spray drying tower, and collect the final curing agent with a particle size of 15 - 40 μm.

[0021] Preferably, the short - chain organic phase - change material microcapsules are prepared by cross - linking microencapsulation of saturated fatty acids and chitosan emulsion with glutaraldehyde, and the particle size of the microcapsules is 5 - 10 μm.

[0022] Preferably, the particle size of the nano - hydroxyapatite is 20 - 50 nm.

[0023] Preferably, the alkali - activated blast furnace slag powder is obtained by activating with 50 wt% NaOH solution for 2 h and then grinding, and the particle size ≤75 μm.

[0024] Preferably, the mass ratio of cross - linked sodium polyacrylate to cellulose nanofibers is 1:0.5.

[0025] Preferably, the emulsification and shearing rate of the shear emulsifier is 3000 rpm, and the cross - linking time is 2 h.

[0026] Preferably, the ultrasonic dispersion treatment is at 20 kHz, with a power of 300 W and a treatment time of 25 min.

[0027] Preferably, the inlet temperature of the spray drying tower is 180°C, the outlet temperature is 80°C, and the particle size of the obtained product is 15 - 40 μm.

[0028] Compared with the prior art, the beneficial effects of the present invention are:

[0029] (1) In the present invention, the microcapsules composed of crosslinked sodium polyacrylate and cellulose nanofibers can form a three-dimensional network structure in the matrix, adsorbing and locking a large amount of water; the microcapsules gradually release water during the cement hydration process, maintaining the internal relative humidity and reducing the surface evaporation rate, thereby ensuring the continuous hydration reaction of cement particles; the phase change fatty acid absorbs and releases latent heat during the melting / solidification process, which can effectively buffer the instantaneous temperature changes during construction and freeze-thaw cycles, reducing the concentration of thermal stress; propylene glycol and silicone emulsion form an anti-freezing film in the aqueous phase and lower the freezing point of water in the capillary pores, jointly inhibiting the formation of ice crystals with the phase change material and reducing the frost heaving damage.

[0030] (2) In the present invention, nano-calcium oxide provides a large number of active Ca 2+ ions, promoting the rapid dissolution and reprecipitation of cement C3S / C2S at low temperatures; magnesium sulfate acts as a crystallization regulator to enhance the initial setting and strength growth rate; the tank slag produces more active silicoaluminates after alkali activation, constructing secondary silicate gel (C–S–H) to enhance the early structure, especially maintaining a high hydration efficiency even in low-temperature environments; nano-HAp can enter the capillary pores and microcracks, providing a large number of nucleation sites as a heterogeneous interface, filling the pores microscopically and promoting the growth of C–S–H; ultrasonic action is used to disperse the particle agglomeration, ensuring the uniform distribution of nano-materials and mineral powder, and then forming a continuous and dense hydration product layer at the entire aggregate-paste interface. Brief Description of the Drawings

[0031] Figure 1 It is a flow chart of a preparation method of a curing agent for cement stabilized macadam for the road base applicable to the Qinghai-Tibet alpine region in the present invention. Detailed Embodiments

[0032] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative work shall fall within the protection scope of the present invention.

[0033] Example 1:

[0034] Please refer to Figure 1 As shown, a curing agent for cement stabilized macadam for the road base applicable to the Qinghai-Tibet alpine region, the curing agent includes by mass percentage:

[0035] 40% crosslinked sodium polyacrylate–cellulose nanofiber composite water-retaining microcapsules, 8% short-chain organic phase change material microcapsules, 5% nano-hydroxyapatite, 25% alkali-activated blast furnace slag powder, 0.5% graphene oxide aqueous dispersion, 10% low-temperature early strength composite agent, 9% environment-friendly anti-freezing long-acting agent, 2% polycarboxylate-based high-range water reducer, 0.5% auxiliary stabilizer.

[0036] Preferably, the low-temperature early strength composite agent is nano-calcium oxide and magnesium sulfate, and the mass fraction percentages of nano-calcium oxide and magnesium sulfate are 60% and 40% respectively;

[0037] The environment-friendly anti-freezing long-acting agent is propylene glycol and silicone emulsion, and the mass fraction percentages of propylene glycol and silicone emulsion are 65% and 35% respectively;

[0038] The auxiliary stabilizer is crosslinked carboxymethyl cellulose and borax, and the mass fraction percentages of crosslinked carboxymethyl cellulose and borax are 70%:30%.

[0039] A preparation method of a curing agent for cement stabilized macadam for pavement base applicable to the Qinghai-Tibet alpine region, comprising the following steps:

[0040] S1. Microencapsulated water-retaining matrix: Mix crosslinked sodium polyacrylate and cellulose nanofibers in deionized water at a solid-water ratio of 1:10, and the mass ratio of crosslinked sodium polyacrylate to cellulose nanofibers is 1:0.5. Heat to 60°C and stir for 45 min, and perform spray microencapsulation to obtain water-retaining microcapsule powder;

[0041] S2. Phase change material microencapsulation: Dissolve the short-chain saturated fatty acid phase change material in hexane, emulsify it with 1 wt% chitosan aqueous emulsion under a shear emulsifier, add glutaraldehyde for crosslinking, and let it stand for 2 h. Elute the solvent and dry to obtain phase change microcapsule powder, and the microcapsule particle size is 5–10 μm;

[0042] S3. Composite colloid preparation: Add the water-retaining microcapsule powder and the phase change microcapsule powder to the water phase at a mass ratio of 1:4, stir at 50°C and 800 rpm for 30 min to obtain a water-retaining-phase change composite colloid;

[0043] S4. Nano-mineral dispersion: Sequentially add alkali-activated blast furnace slag powder, nano-hydroxyapatite with a solid content of 30% (the particle size of nano-hydroxyapatite is 20–50 nm), and 0.8% graphene oxide dispersion to the water-retaining-phase change composite colloid, and perform ultrasonic dispersion treatment to obtain a nano-mineral homogeneous slurry;

[0044] S5. Functional agent compounding: Mix the low-temperature early strength composite agent and the environment-friendly anti-freezing long-acting agent at a ratio of 1:1 and dropwise add them to the nano-mineral homogeneous slurry, maintain stirring at 40°C and 600 rpm for 20 min to obtain a multi-functional composite slurry;

[0045] S6. Construction adaptability optimization: Add polycarboxylate superplasticizer and auxiliary stabilizer to the multifunctional composite slurry, and stir at 200 rpm for 10 min at room temperature to obtain the slurry with optimized construction adaptability.

[0046] S7. Spray drying: Dry the slurry with optimized construction adaptability in a spray drying tower, and collect the final curing agent with a particle size of 15–40 μm.

[0047] Specifically, the emulsification and shearing rate of the shear emulsifier is 3000 rpm, and the crosslinking time is 2 h.

[0048] Specifically, the ultrasonic dispersion treatment is at 20 kHz, with a power of 300 W and a treatment time of 25 min.

[0049] Specifically, the inlet temperature of the spray drying tower is 180 °C, the outlet temperature is 80 °C, and the particle size of the obtained product is 15–40 μm.

[0050] Example 2:

[0051] 1. Batching and construction process

[0052] Material preparation

[0053] Cement: 100 kg of P·O 42.5 ordinary Portland cement

[0054] Curing agent: 2.5 kg (2.5% of the cement mass)

[0055] Fine aggregate (sand): 300 kg

[0056] Coarse aggregate (5–20 mm gravel): 600 kg

[0057] Water: 203 kg according to the water-cement ratio of 0.45

[0058] Mixing process

[0059] Mix the cement, curing agent G, and fine aggregate for 1 min without adding water;

[0060] Add water and coarse aggregate and continue mixing for 2 min;

[0061] Transport the mixture to a 150 mm × 150 mm × 150 mm mold, and compact and level it on a vibrating table;

[0062] After demolding, number it and place it in a constant temperature low-temperature box at –25 °C ± 2 °C and RH 50%.

[0063] 2. The test items are shown in Table 1 below:

[0064] Table 1

[0065]

[0066] 3. The test data and calculations are shown in Table 2 below.

[0067] Table 2

[0068]

[0069]

[0070] Example 3:

[0071] Formulation and construction parameters

[0072] Same as Example 2, but the dosage of the curing agent is changed to 3.0% (3.0 kg) of the cement mass. The test results are shown in Table 3 below:

[0073] Table 3

[0074]

[0075]

[0076] III. The comparative test is shown in Table 4 below

[0077] Table 4

[0078]

[0079]

[0080] Comparison and explanation:

[0081] Compared with traditional sprinkler curing, the water retention rate in Example 2 is increased by 26.2%, the 3-day strength is increased by 50.8%, and the freeze-thaw strength loss rate is decreased by 19.4%;

[0082] Compared with only using conventional polycarboxylate-based water reducers, the water retention rate in Example 2 is increased by 16.8%, the 3-day strength is increased by 23.5%, and the freeze-thaw loss rate is decreased by 9.7%, significantly improving the early strength and durability.

[0083] IV. The technical effects are prominent

[0084] Super water retention: The water retention rate in Example 3 reaches 90.3% at 72 h, far superior to traditional and conventional schemes.

[0085] Low-temperature early strength: The 3-day compressive strength is close to 10 MPa, which can meet the urgent construction period requirements in the alpine regions of Qinghai-Tibet.

[0086] Excellent freeze-thaw resistance: The strength loss rate after 50 freeze-thaw cycles ≤ 7.3%, significantly superior to the comparative example, ensuring the long-term durability of the road surface.

[0087] As can be seen from the above, the microcapsules composed of cross-linked sodium polyacrylate and cellulose nanofibers can form a three-dimensional network structure in the matrix, adsorb and lock water in large quantities; the microcapsules gradually release water during the cement hydration process, maintain the internal relative humidity, and reduce the surface evaporation rate, thereby ensuring the continuous hydration reaction of cement particles;

[0088] The phase change fatty acid absorbs and releases latent heat during the melting / solidification process, which can effectively buffer the instantaneous temperature changes during construction and freeze-thaw cycles and reduce the concentration of thermal stress; propylene glycol and silicone emulsion form an anti-freezing film in the water phase and lower the freezing point of water in the capillary pores, and jointly with the phase change material, inhibit the formation of ice crystals and reduce the frost heave damage;

[0089] Nanoscale calcium oxide provides a large number of active Ca 2+ ions, promoting the rapid dissolution and reprecipitation of cement C3S / C2S at low temperatures; magnesium sulfate is used as a crystallization regulator to increase the initial setting and strength growth rate; the tank slag produces more active silicoaluminates after alkali activation, constructs secondary silicate gels (C–S–H), enhances the early structure, and can maintain a high hydration efficiency especially in low-temperature environments;

[0090] Nanoscale HAp can enter the capillary pores and microcracks, provide a large number of nucleation sites as a heterogeneous interface, fill the pores microscopically and promote the growth of C–S–H; the particle agglomeration is dispersed by ultrasonic action to ensure the uniform distribution of nanomaterials and mineral powders, and then a continuous and dense hydration product layer is formed at the entire aggregate-paste interface.

[0091] In the description of this specification, the description with reference to terms such as "one embodiment", "some embodiments", "example", "specific example" or "some examples" means that the specific features, structures, materials or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in a suitable manner in any one or more embodiments or examples. In addition, without contradiction, those skilled in the art can combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples.

[0092] In the attached drawings of the disclosed embodiments of the present invention, only the structures related to the disclosed embodiments are involved, and other structures can refer to the general design. Without conflict, the same embodiment and different embodiments of the present invention can be combined with each other.

[0093] Although the embodiments of the present invention have been shown and described, for those of ordinary skill in the art, it can be understood that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A curing agent for cement stabilized macadam used in the road base applicable to the Qinghai-Tibet alpine region, characterized in that, The health agent comprises, by mass percentage: 35% - 40% of crosslinked sodium polyacrylate - cellulose nanofiber composite water - retaining microcapsules, 5% - 8% of short - chain organic phase - change material microcapsules, 3% - 5% of nano - hydroxyapatite, 20% - 25% of alkali - activated blast furnace slag powder, 0.5% - 1% of graphene oxide aqueous dispersion, 8% - 10% of low - temperature early - strength composite agent, 6% - 9% of environment - friendly anti - freezing long - acting agent, 1% - 2% of polycarboxylate - based high - range water - reducer, and 0.5% - 1% of auxiliary stabilizer.

2. The curing agent for cement stabilized macadam used for the road surface base in the Qinghai-Tibet alpine region according to claim 1, wherein, The low - temperature early - strength composite agent is nano - calcium oxide and magnesium sulfate, and the mass fraction percentages of nano - calcium oxide and magnesium sulfate are 60% and 40% respectively; The environment - friendly anti - freezing long - acting agent is propylene glycol and silicone emulsion, and the mass fraction percentages of propylene glycol and silicone emulsion are 65% and 35% respectively; The auxiliary stabilizer is crosslinked carboxymethyl cellulose and borax, and the mass fraction percentages of crosslinked carboxymethyl cellulose and borax are 70%:30%; 3. The preparation method of a curing agent for cement stabilized macadam used in the road surface base in the Qinghai-Tibet alpine region according to any one of claims 1-2, characterized in that, It includes the following steps: S1. Mix crosslinked sodium polyacrylate and cellulose nanofibers in deionized water at a solid - to - water ratio of 1:10, heat to 60 °C and stir for 45 min, and perform spray micro - encapsulation to obtain water - retaining microcapsule powder; S2. Dissolve short - chain saturated fatty acid phase - change material in hexane, emulsify it with 1 wt% chitosan aqueous emulsion under a shear emulsifier, add glutaraldehyde for crosslinking, let it stand for 2 h, elute the solvent and dry to obtain phase - change microcapsule powder; S3. Add the water - retaining microcapsule powder A and the phase - change microcapsule powder B to the aqueous phase at a mass ratio of 1:4, stir at 50 °C and 800 rpm for 30 min to obtain a water - retaining - phase - change composite colloid; S4. Sequentially add alkali - activated blast furnace slag powder and nano - hydroxyapatite with a solid content of 30% and 0.8% graphene oxide dispersion to the water - retaining - phase - change composite colloid, and perform ultrasonic dispersion treatment to obtain a nano - mineral homogeneous slurry; S5. Mix the low - temperature early - strength composite agent and the environment - friendly anti - freezing long - acting agent at a ratio of 1:1 and drop - add them to the nano - mineral homogeneous slurry, keep stirring at 40 °C and 600 rpm for 20 min to obtain a multi - functional composite slurry; S6. Add polycarboxylate - based high - range water - reducer and auxiliary stabilizer to the multi - functional composite slurry, stir at room temperature of 200 rpm for 10 min to obtain a slurry with optimized construction adaptability; S7. Dry the slurry with optimized construction adaptability in a spray drying tower, and collect the final health agent with a particle size of 15 - 40 μm.

4. The preparation method of a curing agent for cement stabilized macadam used in the road surface base in the Qinghai-Tibet alpine region according to claim 3, characterized in that, The short - chain organic phase - change material microcapsules are prepared by cross - linking micro - encapsulation of saturated fatty acid and chitosan emulsion, and the particle size of the microcapsules is 5 - 10 μm.

5. The preparation method of a curing agent for cement stabilized macadam for road base applicable to the Qinghai-Tibet alpine region according to claim 3, characterized in that, The particle size of the nano - hydroxyapatite is 20 - 50 nm.

6. The preparation method of a curing agent for cement stabilized macadam for pavement base applicable to the Qinghai-Tibet alpine region according to claim 3, characterized in that, The alkali - activated blast furnace slag powder is obtained by activating with 50 wt% NaOH solution for 2 h and then grinding, and the particle size ≤75 μm.

7. The preparation method of a curing agent for cement stabilized macadam for road base applicable to the Qinghai-Tibet alpine region according to claim 3, characterized in that, The mass ratio of crosslinked sodium polyacrylate to cellulose nanofibers is 1:0.

5.

8. The preparation method of a curing agent for cement-stabilized macadam used for the road surface base in the Qinghai-Tibet alpine region according to claim 3, characterized in that, The emulsification shear rate of the shear emulsifier is 3000 rpm, and the cross - linking time is 2 h.

9. The preparation method of a curing agent for cement stabilized macadam used in the road surface base in the alpine region of Qinghai-Tibet, as claimed in claim 3, is characterized in that The ultrasonic dispersion treatment is at 20 kHz, with a power of 300 W and a treatment time of 25 min.

10. The preparation method of a curing agent for cement stabilized macadam for road base applicable to the Qinghai-Tibet alpine region according to claim 3, characterized in that, The inlet temperature of the spray drying tower is 180 °C, the outlet temperature is 80 °C, and the particle size of the obtained product is 15–40 μm.